Devil's ride west [large type] - Nix, David (Jake Paynter Series, 2022)
"Jake Paynter is in deep trouble. With a $1000 bounty on his head, every law man, bounty hunter, and desperado west of the Mississippi is gunning for him. Jake's plan to lay low with the Shoshone quickly falls apart, but before he can leave for far Yellowstone, his two best friends, Gus Rivers and Stacy Blue, show up with a dilemma. Miners at South Pass City are getting murdered by a man or beast - no one is certain - and his immigrant friends from the Oregon Trail are in danger. Against his better judgment, Paynter travels to the mining fields to bring the culprits to justice. Hiding in an abandoned mine by day and sleuthing by night, Jake begins to unravel the mystery of the deaths. But as adversarial forces close in, Jake must decide whether to escape to isolation or remain and fight for his friends."--